PROGRAM ’KONVERSI MINYAK TANAH KE LPG’ SEBAGAI SUATU TEHNIK PENGURANGAN EMISI - Suarna, Endang (BPPT)
The goal of Government Policy on converting the utilization of kerosene to LPG is to reduce kerosene consumption and fuel oil subsidy. As kerosene has higher pollutants and greenhouse gases emissions rather than LPG, the program also has impact on reducing those emissions that would lead to improving indoor air quality. Higher energy efficiency of LPG stove and more reserve production ratio (R/P) of gas can be attributed to the advantages of utilization of LPG. Indirectly, the conversion kerosene to LPG has another impact on reducing illegal blending between gasoline or diesel with kerosene for transportation sector. The program not only has economical advantages, but also has environmental advantages.Key words: LPG, kerosene, fuel oil subsidy, energy efficiency, indoor air quality